2008
DOI: 10.1016/j.jad.2008.01.026
|View full text |Cite
|
Sign up to set email alerts
|

New episodes and new onsets of major depression in borderline and other personality disorders

Abstract: Background: In the context of much literature and conjecture about the relationship of personality disorders (PD) and major depressive disorder (MDD), this paper uses longitudinal data to assess the frequency with which PD patients, and especially those with borderline personality disorder (BPD), have recurrences (for patients with lifetime histories), or new onsets (for patients without lifetime histories) of MDD. Methods: A sample of 478 PD patients received reliable repeated follow-up assessments over a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 19 publications
6
49
0
1
Order By: Relevance
“…42,43 In addition, older adults manifest maladaptive behaviors and Axis I disorders under acute stress. 35 BPD increases the risk of MDE recurrence, 44 and aging alone does not seem to affect the strength of the relationship between personality disorders and depression. 45 Under stressful situations, temperamental traits might be considered a risk factor for developing episodes of major depression in this age group.…”
Section: Resultsmentioning
confidence: 95%
“…42,43 In addition, older adults manifest maladaptive behaviors and Axis I disorders under acute stress. 35 BPD increases the risk of MDE recurrence, 44 and aging alone does not seem to affect the strength of the relationship between personality disorders and depression. 45 Under stressful situations, temperamental traits might be considered a risk factor for developing episodes of major depression in this age group.…”
Section: Resultsmentioning
confidence: 95%
“…Recent longitudinal studies have shown that Cluster B PDs are associated with a higher risk of developing depressive and anxiety disorders. [21][22][23] Numerous studies have established that depressive symptoms or episodes increase risk of incident cardiovascular disease in community-dwellers. 24 Anxiety disorders also appear to increase risk for coronary heart disease risk, independently of major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…These past comorbidities were included due to high rates of lifetime MDD (Gunderson et al, 2008;Shea et al, 2004) and PTSD (Shea et al, 2004) among individuals with BPD. Similarly, substance use disorders are very common in BPD (Zanarini et al, 2011).…”
Section: Subjectsmentioning
confidence: 99%